(untitled) - Koppelman, Stef J. (Boca Raton, 2006)
Allergens pose a serious risk to consumers, making effective detection methods a priority for the food industry. Bringing together key experts in the field, this important collection both reviews the range of analytical techniques available and their use to detect specific allergens such as nuts, dairy and wheat products. The first part of the book discusses established methods of detection such as the use of antibodies and ELISA techniques. Part 2 reviews techniques for particular allergens. The final part of the book explores how detection methods can be most effectively applied and includes discussions on factors that affect test performance and allergen analysis from a legal perspective.
Keywords: Food allergy,Food hypersensitivity